Has it come to this? : the promises and perils of geoengineering on the brink / edited by J.P. Sapinski, Holly Jean Buck, and Andreas Malm. - Sapinski, J. P.; Buck, Holly Jean, 1981-; Malm, Andreas, 1977- (Nature, society, and culture., 2021)
Now that climate emergency is upon us, claims that geoengineering is inevitable are rapidly proliferating. How did we get into this situation where the most extreme path now seems a plausible development? Is it an accurate representation of where we are at? Who is this 'we' who is talking? What options make it onto the table? Which are left out? Whom does geoengineering serve? Why is the ensemble of projects that goes by that name so salient, even though the community of researchers and advocates is remarkably small? These are some of the questions that the thinkers contributing to this volume are exploring from perspectives ranging from sociology and geography to ethics and Indigenous studies.